Atorvastatin restores imbalance of cluster of differentiation 4 (CD4)+ T cells in immune thrombocytopenia in vivo and in vitro. (25th November 2021) - Xu, Pengcheng; Zhao, Yajing; Yu, Tianshu; Yu, Yafei; Ni, Xiaofei; Wang, Haoyi; Sun, Lu; Han, Panpan; Wang, Lingjun; Sun, Tao; Liu, Xinguang; Zhou, Hai; et al.
Summary: Immune thrombocytopenia (ITP) is an autoimmune haemorrhagic disease, in which the overactivation of T cells is crucial in the pathogenesis. Atorvastatin (AT), a lipid‐lowering medicine, has shown promising immunomodulatory effects in certain inflammatory conditions. However, the immunoregulatory role of AT in ITP remains elusive. To investigate the effect of AT in the treatment of ITP, cluster of differentiation 4 (CD4) + T cells were isolated from patients with ITP and cultured with different dosages of AT. We found that AT significantly inhibited cell proliferation, led to cell cycle arrest, induced apoptosis, and repressed the activation of CD4 + T cells in vitro . ITP murine models were then established, and results showed that AT treatment led to faster recovery of the platelet count to normal and exhibited comparable immunomodulatory function. Furthermore, we found the phosphorylation of mammalian target of rapamycin (mTOR), protein kinase B (AKT) and extracellular signal‐regulated kinase (ERK), as well as activation of rat sarcoma virus (RAS) were all reduced dramatically after AT treatment in vitro . In conclusion, our present study demonstrated that AT could reinstate the functions of CD4 + T cells by inhibiting the excessive activation, proliferation, and survival of CD4 + T cells in ITP via the RAS/mitogen‐activated protein kinase kinase (MEK)/ERK and the mTOR/phosphatidylinositol‐3 kinase (PI3K)/AKT pathway. Therefore, we propose that AT could be used as a potential therapeutic option for ITP by restoring the over‐activated cellular immunity.